Detection of myenteric plexus neurons in dyslipidemic, smoking, and diabetic rats treated with carqueja (Research, Society and Development, 2020)
The plant species Baccharis trimera presents antioxidants that may have neuroprotective effects on the neurons of the myenteric plexus. Thus, the aim of the present study was to investigate possible quantitative alterations in the myenteric plexus neurons and in the glycemic and lipid profile of 25 rats with 90 days old, exposed to smoking, a hypercholesterolemic diet, and with diabetes mellitus induced by streptozotocin during four weeks, and then treated with different doses of carqueja extract for two weeks. The myenteric plexus neurons were stained with basic Giemsa and using the NADPH-diaphorase histochemistry protocol. In the study conditions, there was a significant reduction in the number of total neurons between the groups treated with carqueja and the positive control, stained with the Giemsa. In contrast, there was no significant difference in the number of neurons of the inhibitory subpopulation between the groups treated with carqueja and the negative control, evidenced by the NADPH-diaphorase histochemistry. At the 30mg/kg dose there was a reduction in the cholesterol and triglyceride levels. Based on the results, Baccharis trimera presented no neuroprotective or hypoglycemic effect, although the nitric subpopulation has proven more resistant to the deleterious effects of diabetes, smoking, and the hypercholesterolemic diet.